Clinical instructors’ perceptions of virtual reality in health professionals’ cardiopulmonary resuscitation education - Wong, Marie Ann Mae En (2019)
Objectives: Cardiopulmonary resuscitation (CPR) is lifesaving. Yet, cardiac arrest survival remains low despite CPR intervention. Education has been highlighted as a strategy to overcome this issue. Virtual Reality technology has been gaining momentum in the field of clinical education. Published studies report benefits of virtual reality for CPR education; yet, perceptions of CPR instructors towards virtual reality remain unexplored. CPR instructors are key stakeholders in CPR education and their perceptions are valuable for the design and adoption of virtual reality-enhanced learning. The purpose of this study is therefore to understand the perceptions of CPR instructors towards using virtual reality for health professionals’ CPR education. The aim was addressed via three research questions: (1) What are the perceptions of CPR instructors towards current health professionals’ CPR education? (2) What are the perceptions of CPR instructors towards features of virtual reality ideal for health professionals’ CPR education? (3) What are the perceptions of CPR instructors towards the potential role of virtual reality in health professionals’ CPR education? Methods: A total of 30 CPR instructors were surveyed on their views towards current health professionals’ CPR education and the use of virtual reality for health professionals’ CPR education, before and after interacting with a CPR virtual reality simulation. Responses were analysed using interpretative thematic analysis. Results: CPR instructors perceived current health professionals’ CPR education as limited due to unideal test preparation (resources, practice, motivation, and frame of mind) and performance. They perceived fidelity, engagement, resource conservation, and memory enhancement as features of virtual reality ideal for health professionals’ CPR education. Virtual reality was viewed by CPR instructors as having potential as a blended learning tool, targeting both ‘novice’ and ‘experienced’ health professionals. Conclusion: The study highlighted the gaps in current health professionals’ CPR education that can be addressed using virtual-reality-enabled learning. Future research could investigate virtual reality simulations with features desirable for CPR education of target populations.